2022
DOI: 10.1039/d1sc05484h
|View full text |Cite
|
Sign up to set email alerts
|

HSA-Lys-161 covalent bound fluorescent dye for in vivo blood drug dynamic imaging and tumor mapping

Abstract: The specific combination of human serum albumin and fluorescent dye will endow superior performance to the coupled fluorescent platform for in vivo fluorescence labeling. In this study, we found that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In 2022, our research group reported turn-on fluorescent probe 98 (SS-1) covalently bound to albumin (Figure 29), which enabled long-term and real-time fluorescence detection during in vivo imaging. 162 At the same time, 98-labeled HSA as a conjugated fluorescent probe interacted with the drug and caused a significant increase in fluorescence. This was the first in situ monitoring of the ibuprofen concentration in blood by fluorescence analysis.…”
Section: Probe Combined With Hsa For Optical Imaging and Therapymentioning
confidence: 99%
“…In 2022, our research group reported turn-on fluorescent probe 98 (SS-1) covalently bound to albumin (Figure 29), which enabled long-term and real-time fluorescence detection during in vivo imaging. 162 At the same time, 98-labeled HSA as a conjugated fluorescent probe interacted with the drug and caused a significant increase in fluorescence. This was the first in situ monitoring of the ibuprofen concentration in blood by fluorescence analysis.…”
Section: Probe Combined With Hsa For Optical Imaging and Therapymentioning
confidence: 99%
“…Methods such as immunochemistry, protein mass spectrometry, bromocresol green (BCG), and bromocresol purple (BCP) have been developed for the quantitative detection of HSA, but they suffer from complicated operation and are costly. Fluorescence sensing and imaging is a noninvasive detection approach that has become popular in recent decades, especially in small-molecule-based probes that exhibit the advantages of high sensitivity, selectivity, multicolor imaging, high background contrast with high signal-to-noise ratio in situ , etc. To date, the small-molecular fluorescent probes developed for HSA can be categorized into noncovalent and covalent binding modes. , It has been suggested that covalent binding exhibits better selectivity and stability to resist interference from small biomolecules and drugs. ,,, Ajayaghosh et al developed self-assembling dyes that form nonfluorescent nanoparticles, and HSA can selectively disassemble and covalently bind to generate a fluorescent response . He et al orthogonally functionalized HSA using covalent and supramolecular approaches to modular peptides, achieving specific optical visualization and photodynamic ablation of malignant liver tumors of human origin .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few of them exhibit the potential to probe the drug binding site on HSA (Table S1†). 14 For example, Zhen Zou et al have recently presented a perylenediimide probe that can specifically target the binding site of an anti-convulsion drug tiagabine hydrochloride (TGB) on HSA, resulting in significant fluorescence changes. On this basis, a fluorescence assay has been developed for quantitatively analyzing TGB.…”
Section: Introductionmentioning
confidence: 99%